'Use your white voice': race, sound, and genre in Sorry to Bother You. Issue 1 (2nd January 2022) - Maurice, Alice
ABSTRACT: Looking primarily at Boots Riley's Sorry to Bother You (2018), this essay explores the way race informs the relationship between the 'body genres' of comedy and horror. Riley's film works through genre hybridity and 'genre switching', and this essay examines the links between the film's genre reflexivity and the other kind of reflex – the 'involuntary bodily response'. By locating its critique – by assaulting genre – at the level of sound, the film offers a way for us to think about our own involuntary responses, our own reflexes, when it comes to racial categories and racial identity. Looking particularly at the 'white voice' device, I argue that the film's formal and stylistic strategies also enact a deeper critique, revisiting and re-activating the ways in which the basic conditions of the cinematic illusion have been suffused with racialized meaning in American film. In particular, the film's strategies reflect how an imaginary Blackness has worked to generate genre and to animate the links between genres – especially comedy and horror. By reflecting on embodiment and disembodiment – and the synchronization of sound and image – Sorry to Bother You exploits genre, working it like a puppet, or like a monstrous filmic body.